Apollo 11: first moon landing - Cole, Michael D. (Springfield, NJ Enslow Publishers, Inc., 1995)
Summary: The author recreates this exciting event using detailed descriptions and actual dialogue between the astronauts and MissionControl.
Keywords: Project Apollo (U.S.).; Space flight to the moon; Series: Countdown to space